Analysis of Ferrous on Ten-Eleven Translocation Activity and Epigenetic Modifications of Early Mouse Embryos by Fluorescence Microscopy. (7th February 2016) - Zhao, Ming-Hui; Liang, Shuang; Guo, Jing; Choi, Jeong-Woo; Kim, Nam-Hyung; Lu, Wen-Fa; Cui, Xiang-Shun
Abstract: Iron is an essential trace element that plays important roles in the cellular function of all organs and systems. However, the function of Fe(II) in mammalian embryo development is unknown. In this study, we investigated the role of Fe(II) during preimplantation embryo development. Depletion of Fe(II) using thiosemicarbazone-24 (TSC24), a specific Fe(II) chelator, rescued quenching of the Fe(II)-sensitive fluorophore phen green-SK. After in vitro fertilization, TSC24 significantly reduced the cleavage rate as well as blastocyst formation. The hatch rate of blastocysts was also reduced with 1 pM TSC24 treatment (20.25±1.86 versus 42.28±12.96%, p <0.05). Blastocysts were cultured in leukemia inhibitory factor-free mouse embryonic stem cell culture medium with or without TSC24, and those with depleted Fe(II) displayed delayed attachment and lost the ability to induce embryoid body formation. To further explore the mechanism of Fe(II) in embryo development, we assessed the expression of 5-hydroxymethylcytosine (5hmC) and OCT4 in the pronuclear and blastocyst stages, respectively. We observed that Fe(II) reduced 5hmC and OCT4 expression, which could be explained by low ten-eleven translocation (TET) enzyme activity induced by TSC24 treatment. These findings demonstrate that Fe(II) is required for mammalian embryo development and that it facilitates the process via regulation of TET activity.